Antiinflammatory activity of natural dietary flavonoids - De Souza, Matheus Chiaradia [UNESP]; De Castilho, Ana Laura Tironi [UNESP]; Tarran, Carolina Mendes [UNESP]; Zabeu, Mateus Souza [UNESP]; Teixeira, Leonardo de Liori [UNESP] (Elsevier, 2021)
The antiinflammatory activities of medicinal plants are generally exerted through their secondary metabolites, which are divided in three major classes: terpenes, phenolic compounds, and alkaloids. Flavonoids are phenolic compounds naturally occurring in fruits, vegetables, seeds, barks, and several medicinal plants. Flavonoids present a common structure (C6-C3-C6), where both extremities are aromatic rings interconnected by a linear chain of three carbons. This chapter investigated the antiinflammatory potential of flavonoids from the natural diet, aiming to evidence how this natural compounds influence our health and diseases. We also focused in the main causes of human death, which are cardiovascular diseases, diabetes, and gastrointestinal diseases. The highlighting of flavonoid uses could direct future researches in the field, aiming to develop a phytomedicine that could be used in several conditions.
Keywords: Antiinflammatory activity; Cardiovascular diseases; Diabetes; Dietary flavonoids; Gastrointestinal diseases; Natural compounds; Phytomedicine